HIV reservoirs in vivo and new strategies for possible eradication of HIV from the reservoir sites - Nitin K Saksena (Dove Medical Press, 2010)
Nitin K Saksena, Bin Wang, Li Zhou, Maly Soedjono, Yung Shwen Ho, Viviane ConceicaoRetroviral Genetics Division, Center for Virus Research, Westmead Millennium Institute, The University of Sydney, Westmead, NSW, Sydney, AustraliaAbstract: Even though the treatment of human immunodeficiency virus (HIV)-infected individuals with highly active antiretroviral therapy (HAART) provides a complete control of plasma viremia to below detectable levels (<40 copies/mL plasma), there is an unequal distribution of all antiretroviral drugs across diverse cellular and anatomic compartments in vivo. The main consequence of this is the acquisition of resistance by HIV to all known classes of currently prescribed antiretroviral drugs and the establishment of HIV reservoirs in vivo. HIV has a distinct advantage of surviving in the host via both pre-and postintegration latency. The postintegration latency is caused by inert and metabolically inactive provirus, which cannot be accessed either by the immune system or the therapeutics. This integrated provirus provides HIV with a safe haven in the host where it is incessantly challenged by its immune selection pressure and also by HAART. Thus, the provirus is one of the strategies for viral concealment in the host and the provirus can be rekindled, through unknown stimuli, to create progeny for productive infection of the host. Thus, the reservoir establishment remains the biggest impediment to HIV eradication from the host. This review provides an overview of HIV reservoir sites and discusses both the virtues and problems associated with therapies/strategies targeting these reservoir sites in vivo.Keywords: HIV, HAART, reservoirs, compartmentalization, elimination strategies for reservoirs, AIDS